Symptomatic and functional outcomes after treatment with paliperidone palmitate 3-month formulation for 52 weeks in patients with clinically stable schizophrenia - Maria Paz Garcia-Portilla; Pierre-Michel Llorca; Giuseppe Maina; Vasilis P. Bozikas; Halise Devrimci-Ozguven; Sung-Wan Kim; Paul Bergmans; Irina Usankova; Katalin Pungor (SAGE Publishing, 2020)
Background: Paliperidone palmitate 3-monthly (PP3M) formulation is a long-acting, injectable antipsychotic treatment approved in many countries worldwide for the maintenance treatment of adult patients with schizophrenia. This single-arm, open-label, phase IIIb study evaluated the efficacy and safety of converting patients with schizophrenia stabilized with paliperidone palmitate 1-month (PP1M) to PP3M in a naturalistic clinical setting. Methods: After screening (days -7 to 1), patients were converted from PP1M (50-150 mg eq.) to PP3M (175-525 mg eq.), and entered a 52-week, flexible-dose PP3M treatment period. The primary efficacy endpoint was symptomatic remission (SR) (Andreasen criteria) at last observation carried forward (LOCF) endpoint. Results: Patients ( n  = 305) received PP3M, of whom 291 (95.4%) completed the study. Doses of PP3M remained stable during the 12-month treatment period, and changes in dose were uncommon. Overall, 56.8% of patients [95% confidence interval (CI): 51.0, 62.4] achieved SR, and 31.8% achieved both symptomatic and functional remission (Personal and Social Performance scale total score > 70) at LOCF endpoint. Secondary endpoint results were generally consistent with primary endpoint results. There were improvements in Positive and Negative Syndrome Scale total, subscale and Marder factor scores, and also Clinical Global Impression-Severity and -Change scores from baseline to LOCF endpoint. Carer burden was reduced, and the proportion of patients requiring hospitalization for psychiatric reasons decreased from 13.5% in the 12 months prior to baseline to 4.6% during the treatment period. No new safety signals were identified. Conclusion: Results from this naturalistic study were similar to those observed in previous randomized clinical trials of PP3M and underline the importance of continuous maintenance treatment in patients with schizophrenia.